Optimisation and evaluation of zinc in food samples by cloud point extraction and spectrophotometric detection / Nurul Azwa Mohd Azizi … [et al.] - Mohd Azizi, Nurul Azwa; Rahim, Nurul Yani; Ramachandran, Muggundha Raoov; Asman, Saliza (Faculty of Communication and Media Studies (FCMS), Universiti Teknologi MARA, 2019)
The cloud point extraction (CPE) method was developed to determine the zinc prior to Ultraviolet-visible (UV-Vis) spectrophotometry detection. Triton X-100 was applied as extractant based on the complexation reaction of Zn(II) ions with ethylenediaminetetraacetic acid (EDTA). Under optimal conditions, the CPE was used to determine the concentration of zinc in canned food samples. The amounts of zinc found in the food samples were in the range of 0.005-0.007 mg/L with relative standard deviation (RSD) of < 8 %. This confirmed that the proposed CPE method is suitable for the determination of zinc in food samples, indicating the concentration of zinc was within the permissible limit.